2015
DOI: 10.1309/ajcpqprnib54wfkj
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals Data Mining

Abstract: The presented statistical algorithm is shown to be an accurate and practical tool for reference interval calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…However, some authors favour the indirect method as the results are clinically relevant and much simpler for an individual laboratory to implement than the time-consuming direct a priori method ( 23 , 24 ). Furthermore, a recent study has suggested that an indirect method can be as accurate as a direct method when the right indirect method is used ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors favour the indirect method as the results are clinically relevant and much simpler for an individual laboratory to implement than the time-consuming direct a priori method ( 23 , 24 ). Furthermore, a recent study has suggested that an indirect method can be as accurate as a direct method when the right indirect method is used ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the indirect approach of deriving reference intervals has gained interest, where secondary data sources such as hospital pathology records 14 and pathology laboratory databases 15 are explored as alternative populations 13 . Through use of stringent inclusion criteria to derive a ‘healthy’ population 16 and/or through novel statistical methods 17 , secondary data sources are proving to be a viable option.…”
Section: Introductionmentioning
confidence: 99%
“…The usual methods for removing incorrect values include: the criterion of 3σ [22], Chauvenel criteria [23], Grubbs criterion [24], and Dixon criterion [25]. All of the methods have been established by experts' subjective experience, and thus far, no unifying rules [26] exist.…”
Section: Electrolysis Process and Problemmentioning
confidence: 99%